PEMBEKALAN TENTANG TIPS MEMILIH JURUSAN YANG SESUAI BAGI SISWA SMA LAMAHOLOT, JAKARTA BARAT - Miharni Tjokrosaputro (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
In general, high school graduates aspire to continue their education at the university level. Many high school students, on the other hand, are undecided about which college major is best for them. As a result, the goal of this community service program is to assist Lamaholot High School students in selecting the appropriate major for furthering their education in college so that they can have a brighter future. The strategy employed in this activity is a means of counseling students from Lamaholot High School in the Kembangan neighborhood of West Jakarta on major selection. Google Meets will carry out the deployment of this operation in 1 November 2021. This community service activity begins with a briefing and motivational counseling to improve Lamaholot High School students' interest in studying, the ins and outs of college life, and the division of majors in the faculty of economics and business, followed by a question and answer session. The output of this program is proceeding.